A China-centered bibliometric study of cooking fumes research with an international comparative perspective - Duan, Huan; Zhang, Gangfeng; Duan, Lian; Lin, Ziyin; Bu, Mengya; Guan, Jie; He, Tianxiang; Zhao, Mengchen; Guo, Yaoguang (Frontiers in Environmental Science, 2026)
IntroductionThe rapid growth of the global catering industry has established cooking fumes as a significant urban air pollutant and public health concern. China, with its distinctive culinary practices, is a prolific contributor to this field. However, a systematic, data-driven understanding of the structure and evolution of this vast Chinese research output, contextualized within the global landscape, remains lacking.MethodsTo address this gap, this China-centered bibliometric study analyzed 552 Chinese and English publications from the China National Knowledge Infrastructure and Web of Science Core Collection databases (1996–2024) using CiteSpace.Results and DiscussionOur findings reveal a clear epistemological divergence: research in China is predominantly policy-driven and technology-oriented, evolving through stages towards integrated multi-pollutant governance. In contrast, international research is characterized by a sustained, health-risk-driven paradigm focused on exposure assessment and toxicological mechanisms. Analysis of collaboration shows a decentralized network with Chinese institutions forming a highly productive yet internally focused core. Critically, the research hotspots are highly complementary: Chinese studies excel in macro-level emission control and technology development, whereas international scholarship leads in micro-level chemical speciation and health risk assessment. This study not only maps Chinese distinct research trajectory against global trends but also identifies strategic pathways for synergistic, targeted international collaboration and interdisciplinary integration.